STUDIES ON FOLLICULAR SIZE AND OOCYTES RECOVERY RATE FROM BUFFALO OVARIES BY SLICING METHOD - Mistry , C N; Dhami , A J (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A total of 456 ovaries of Surti buffaloes were obtained freshly from the local slaughter house and were transferred within 1-2 hours to the laboratory in normal saline at 30-35°C. The ovaries selected were without functional corpus luteum. An average number of follicles of small, medium and large size found per ovary were 0.82, 0.48 and 0.24, respectively, with an overall mean of 1.55. The distribution of small, medium and large follicles was found to be 53.18, 31.12 and 15.70 per cent, respectively. The slicing method of oocyte recovery employed yield a total of 1409 oocytes from these ovaries, with on an average recovery rate of 3.09 oocytes per ovary. The average recovery of grade A, grade B and grade C oocytes was 1.02, 1.22 and 0.85, respectively. The study demonstrated that slicing of the ovarian surface follicle is a convenient and effective method for collecting a high yield of buffalo follicular oocytes for in vitro maturation and embryo production.
Keywords: Buffalo; Abattoir ovaries; Follicular size; Slicing; Oocyte recovery